Analyzing the dimensions and components of organizational culture based on normative and individual variables in the managers of education headquarters in Tehran province - mohammad bermeh; Mohammad Naghi Imani; Saeed Alizadeh; Babak Nasiri; Reza Sourani (Institute of Management fekrenoandish, 2023)
The purpose of the current research is to analyze the dimensions and components of organizational culture based on normative and individual variables in the managers of education headquarters in Tehran province. According to its purpose, the research method is applicable; and in terms of execution method, it is qualitative, descriptive-exploratory; and in terms of its nature, it is among foundation data research. The statistical population of this research includes 12 experts who are well-informed and proficient in the subject of research in the field of management and have a valid scientific background in this field. Sampling method used in this research was non-random purposeful. The method of data collection is referring to documents, semi-structured interviews and questionnaires. For data analysis, Atlas ti software was used to code the interviews. The results showed that in the normative dimension, there are 10 categories: organizational justice, work maturity, ambiguity avoidance, external supervision, decision-making, job promotion, masculinity or feminism, concentration (power distance), customer orientation, productivity with 57 indicators; and in the Individual dimension also has 10 categories: sense of belonging, responsibility, individual creativity, communication, participation (teamwork), identity, self-control, motivation, conflict, interaction in 61 indicators and in 6 categories that include causal conditions, communication conditions, background factors, intervener factors, strategies, consequences were identified.Extended abstractIntroductionJust as people in the society have certain beliefs, values ​​and behaviors that represent their personality; organizations also have common assumptions and basic beliefs that shape their culture. Culture has been defined as the set of spiritual achievements of a nation. Culture is a human invention and made by human hands. This finding reflects the existence and identity of a society (Mirza Mohammadi, 2021). Organizational culture is the personality of the organization and it is considered as the basic infrastructure for transformation and change, and managers should understand its relationship with national culture and strive for organizational cohesion by taking advantage of its strategic role. Organizational culture is an interwoven set of basic assumptions, common inferences and collective wisdom that is formed in the context of previous experiences and findings in facing internal or external issues and serves as a guiding light and an invigorating source plays a role in shaping the behavior of employees and architecture of the present and future of the organization (Mohammadiyan & Shahsavari, 2019).Education is a continuous activity, comprehensive and for everyone, which leads to human growth and development, cultural enrichment and the excellence of society, and therefore, innovation should always be created in it. In other words, education is not specific to an exclusive period and time of life and has no time limit, so it must always be renewed and updated (Safaei et al, 2020). For organizational innovation, development and transformation, one of the important organizational conditions that must be considered in policies and implementation of programs is related organizational culture. The author's many years of experience in executive affairs shows that lack of paying attention to organizational culture has not always led to the desired results of innovation, development, organizational transformation and change in organizations (Hamzeh & Hamzeh, 2016). An organizational culture able to respond to environmental changes can lead to optimal organizational performance.According to the above materials, the researcher asked the main question: what are the dimensions and components of organizational culture based on normative and individual variables in the managers of education headquarters in Tehran province? Theoretical FrameworkOrganizational CultureCulture is a set of customs, standards and individual and social behaviors; therefore, while culture is the effect of many parts of religious views, it is also considered the cause of many conditions and situations. Due to the progress of communication tools and the ever-increasing expansion of their use in many social phenomena and developments, the role of culture has become far greater than in the past; in such a way that culture now plays a decisive role at the domestic, regional and international levels and is one of the tools that governments use to achieve their goals and objectives; in this way, cultural dominance is not a new phenomenon. Cultural policy in the general and customary sense includes a set of goals, principles, priorities and executive policies (Mirza Mohammadi, 2021).Normative and individual variablesIn the conceptual definition of norms, most sociologists are more or less unanimous that norms (forms) are the rules of social behavior that guide a person in social actions. Observing these patterns and rules of behavior expected by the society's culture, and avoiding them is punishable (Khabbaz Yazdiha et al, 2020).Zebardast et al, (2022) investigated the relationship between the transformational leadership factors of educational group managers on the effectiveness of university faculty members through organizational culture. The results showed that the relationship between transformational leadership style of managers and organizational culture was significant and the mediating variable of organizational culture has a significant effect on the relationship between transformational leadership style and the effectiveness of faculty members. It can be said that transformational leadership does not have a direct and significant effect on effectiveness in the final research model. However, transformational leadership affects the effectiveness of faculty members through organizational culture.Yusefi et al, (2022) investigated the impact of individual and normative variables on ethical leadership. The results of the research show that value, job satisfaction, motivation, personality, creativity, components were individual components, and organizational communication, organizational culture, organizational structure, decision-making styles, roles and expectations, goals and strategy were normative components that had a significant impact on ethical leadership.Research methodologyThis research is applicable in terms of purpose, qualitative in terms of execution method: descriptive-exploratory type, and data-based in terms of its nature. The statistical population includes 12 experts and specialists who are well-informed and proficient in the subject of research in the field of management, and have a valid scientific background in this field. Non-random purposeful sampling method is used to determine the samples and determine the experts.Research findingsThree types of coding were used to analyze the data obtained from the interview as well as theoretical foundations, which are: open coding, axial coding and selective coding. For analysis, Atlas ti software was used to code the interviews. The results showed that in the normative dimension, 10 categories were identified: organizational justice, work maturity, ambiguity avoidance, external supervision, decision-making, job promotion, masculinity or feminism, concentration (power distance), customer orientation, productivity with 57 indicators; and in the individual dimension also 10 categories: sense of belonging, responsibility, individual creativity, communication, participation, identity, self-control, motivation, conflict, interaction in 61 indicators, and in 6 categories that include causal conditions, communication conditions, background factors, intervener factors, strategies, consequences.ConclusionThe present research was conducted with the aim of analyzing the dimensions and components of organizational culture based on normative and individual variables in the managers of education headquarters in Tehran province. The results of this research are correspond with the results of Turki et al, (2021), Eimani et al, (2021), Van Dung HA (2020), Yusefi et al, (2020), Mohebbi et al, (2023), Zebardast et al, (2022). Mohebbi et al, (2023) showed that in educational organizations, organizational culture plays an important role in producing teamwork culture and achieving the benefits of the process of participation and collaboration.